Clinical Performance of Extra-Short (≤5.5 mm) Compared to Longer Implants Splinted under the Same Prosthesis: A Randomized Clinical Trial - Eduardo Anitua; Adriana Montalvillo; Asier Eguia; Mohammad Hamdan Alkhraisat (MDPI AG, 2024)
Objective: This randomized controlled split-mouth trial compared the performance of 5.5 mm length implants (test group; TG) splinted within the same fixed prosthesis as longer implants (≥6.5 mm; control group; CG) in posterior regions. Methods: The primary hypothesis was that implant length does not affect marginal bone loss (MBL) one year post-implantation, while the secondary hypotheses included implant survival, peri-implant clinical variables, and prosthetic complications. Fifteen patients (eight males, seven females) with a mean age of 67 ± 9 years were included. Results: No significant difference in the implant position between groups (p = 0.808) was observed. Implant diameters ranged from 3.00 to 4.25 mm, and the most common bone type was type I (67%). Bone density (p = 0.574) and implant insertion torque (p = 0.888) were similar between groups. Mesial MBL (mean: −0.1; range: −1.19 to 0.24 for TG, and −0.03; −1.75 to 0.45 for CG; p = 0.955) and distal MBL (mean: −0.05; range: −1.41 to 0.27 for TG, and 0.08; −1.45 to 0.72 for CG; p = 0.118) did not show statistical differences. There were no implant failures or technical complications. Conclusions: These findings suggest that 5.5 mm length implants could be a viable option for use in posterior regions, providing similar clinical outcomes to longer implants one year post-implantation.